(untitled) (Journal of Economic Research & Business Administration, 2015)
This article concerns the questions of development of approaches to definition of an industrial policy. Industrial policy of state as the part of the general economic policy is one of the most disputable concepts. The analysis of the economic literature carried out by the author shows that the economic and industrial policy of concept not the identical. Along with these terms concepts «the industrial policy» and «the scientific and technical policy» are mentioned.